91 PIMS-TS: the psychological needs of families admitted to intensive care. (15th December 2021) - Freeman, Anita; Ovin, Felicia; Bird, Annie; Galloway, Anna; Sweet, Rebecca; Robertson, Anna; Clisby, Holly; Gardner, Jennifer; Perscott, Natasha; Devaraj, Ramsay; Calissano, Frederica; Berger, Zoe
Abstract : Background: Paediatric Inflammatory Multisystem Syndrome (PIMS-TS) is a rare inflammatory condition affecting children and young people (CYP) weeks after infection with the COVID-19 virus. The aim of this study was to understand the potential psychological needs of these families. Methods: PIMS-TS patients and their parents admitted to the hospital between April 2020 and May 2021 were reviewed by a psychologist 6–8 weeks post discharge, as part of their clinical care. Young people over the age of 7 were asked to complete 2 measures for psychological distress and PTSD symptoms (CRIES-13 and PIED) and their parent/carer completed a measure of PTSD symptoms (IES-R). Ethical approval was not required for this study. Results: 118 CYP and parents/carers who were admitted to GOSH were screened 6–8 weeks post discharge. 85 of the 118 CYP were aged 8 or over. 76.8% (n=91) of parents/carers completed the IES-R, 78% (n=66) of CYPs completed the PIED, and CRIES. 15% (n=10) of CYPs scores on the PIED suggested they were at risk of anxiety and depression. 24% (n=16) of CYPs reported clinically significant difficulties for PTSD on the CRIES-13, placing them in high probability of for a diagnosis of PTSD. 35% of parents/carers met the threshold for clinical concern on IES-R, with 23% (n=21) scoring in the range for a likely diagnosis of PTSD. Discussion: The findings of both the self-report screening questionnaires, indicate that significant number for CYP and their parent/carers are at risk of developing symptoms of psychological distress and trauma in 6–8 week period post discharge after PIMS-TS admission. Conclusion: The result of this study clearly show identification of high levels of trauma and emotional distress for the CYP and their parents and carers, and a potential need for ongoing psychological support to be provided as part of on-going care.